Psychological Effects of COVID-19 Pandemic among the General Population of India - Kumar, Shishir; Shree, Shubham; Kumar, Sanjay (Archives of Men's Health, 2021)
Introduction: C0VID-19 outbreak was declared as a pandemic in 2019 by the World Health Organization (WHO) with a global spread and undefined course. COVID-19 has created great fear and panic all over the world creating mental and physical distress. Looking at the adverse effects of the pandemic, we aimed to assess the psychological conditions of the general population residing in various states of India as a result of the nation-wide lockdown and quarantine in COVID-19. Materials & Methods: This study is a descriptive, cross-sectional, anonymous online survey. A self-rated structured questionnaire was made through Google form. Snowball sampling technique was used. Results: 53.2% of the respondents were men while 46.8% were women. 92.5% resided in urban areas. A comparison between the male and female respondents was made in the various domains and we found that 28.3% of men and 30.2 % of women were affected to a greater extent by the pandemic whereas 24.6% of men were worried about the financial loss. 10.2% of the women reported to feel depressed in the last two weeks while only 7% of the men were irritated. 51.9% and 44.9% of men and women considered it important to take actions for preventing Corona Virus Disease. Conclusion: Stress, anxiety and depression among the general population was found to be moderately present although all the safety guidelines were followed along with the lockdown. The participants had a good level of awareness regarding preventive aspects as well.